Studi Sistem Kendali pada Reaktor C4001 Cycle Gas dan Atmosfer (ATM) Blowdown berbasis Distributed Control System (DCS) di PT Chandra Asri Pacific - Alimuddin, Alimuddin; Utomo, Hans; Arafiyah, Ria; Santoso, Muhammad Iman (Universitas Sultan Ageng Tirtayasa, 2024)
This research explores the control system for the Reactor in the gas cycle and atmosphere blowdown process at PT Chandra Asri Pacific. The focus is on function, performance and temperature control in the Reactor reaction process. The results show a stable and optimal control system analysis. The actual temperature data in conditions 1 to condition 4 shows values of 64.6 ˚C, 82.3 ˚C, 59.5 ˚C, 65 ˚C respectively. The operator sets the set point for the optimal control system process on the Reactor with a target value in condition 1 of 65 ˚C, condition 2 of 65 ˚C, condition 3 of 65 ˚C, condition 4 of 65 ˚C. In conclusion, the Reactor gas cycle control system atmosphere to improve optimal process quality and efficiency of processes and systems in the Reactor which can reach the desired temperature in every condition which shows positive results in optimizing the Reactor control system.